Why Atlanta?: a case study of how place produces intersectional social movement groups. Issue 10 (2nd October 2020) - Peretz, Tal
Abstract: The role of place is undertheorized in the literature on intersectional social movements; this study uses Atlanta, Georgia as an exemplary case study of how the characteristics of geographical areas shape the possibilities for intersectional social movement organizing. Atlanta is home to a rare trend of men's gender justice groups that organize around one or more additional intersecting identities (e.g. race, sexuality, religion). Across the country there are groups like Men Can Stop Rape and Men Against Sexual Violence, but Atlanta has Black Men for the Eradication of Sexism, Muslim Men Against Domestic Violence (MMADV), and the Sweet Tea Southern Queer Men's Collective. Based on a year of participant-observation and interviews with MMADV and Sweet Tea, this paper illustrates how local grassroots activism is shaped by four types of interweaving place-based factors: demographic, geographic, cultural, and institutional. By enabling necessary precursors, these factors combine to create an environment where multiple intersectionally-organized men's gender justice groups could form, independently of each other, despite being extremely uncommon elsewhere in the country. The article develops a model for theorizing about intersectionality, space and place, social movements and activism, and contemporary feminism, as well as contributing to knowledge about activism in the understudied context of the Southern city.